Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board - Bhat, R. V.; Singh, Man Mohan (Indian Forester, 1955)
Laboratory experiments on the production of pulps from twisted chir (Pinus longifolia Roxb.) by the sulphate process for wrapping papers are described. Results of pilot plant experiments are also included. Wrapping papers were prepared on the pilot plant from 1OO% twisted chir sulphate pulp, a mixture of 70% chir sulphate pulp and 30% chir mechanical pulp, a mixture of 69% chir sulphate pulp and 31% bagasse soda pulp, and 100% bagasse soda pulp. A sample each of the wrapping papers from these four furnishes are appended to this bulletin. The average fibre length of the twisted chir was 4.79mm. This investigation has shown that twisted chir is a useful fibrous raw material for the manufacture of wrapping papers.